Constitutional Concepts for the Rule of Law: A Vision for the Post-Monarchy Judiciary in Nepal - David Pimentel (Washington University Global Studies Law Review, 2010)
A new government has taken power in Nepal. Intent on replacing the monarchical Hindu state with a secular democracy, it has promised a new constitution. Although the Nepali government is currently operating under an Interim Constitution, it remains to be seen what the post-monarchy judiciary will look like. Those involved in the drafting should pay careful attention to how specific provisions for court governance will impact both institutional and decisional judicial independence. The Interim Constitution calls for a judicial council but not a sufficiently independent one. The Interim Constitution also allows broad exercise of emergency powers, depriving the courts of jurisdiction over the legality or constitutionality of such exercises — a particularly disturbing flaw given the history of abuse of emergency powers in Nepal. These, along with an array of other concerns that otherwise threaten to undermine the independence and effectiveness of the third branch of government in Nepal, can and should be corrected in the new constitution. This Article sets forth those concerns and suggests solutions for each. Nepal's prospects for the rule of law may depend on how well the new constitution's drafters follow this punch-list of issues and principles as they establish the constitutional framework for the new Nepali judiciary. Reprinted by permission of the publisher.
Keywords: Constitutional crises; Rule of law; Judicial independence; War & emergency powers; Judicial process